Telomerase recognizes its template by using an adjacent RNA motif - Miller, Michael C. (The National Academy of Sciences, 2002)
Telomerase adds telomeric repeats to chromosome 3′ ends, forestalling the cellular senescence, apoptosis, and genomic instability that result from telomere loss caused by incomplete DNA replication. The telomerase ribonucleoprotein is dedicated to synthesis of tandem, simple-sequence repeats by virtue of its specialization for copying only a specific template region within the integral RNA. Here, using circularly permuted variants of Tetrahymena thermophila telomerase RNA, we identify the features that allow recognition of the template region within the RNA. We engineered a template-less telomerase ribonucleoprotein that can position and reverse transcribe an exchangeable RNA oligonucleotide template accurately. Only a short “template-recognition” element sequence tag is required to direct efficient use of adjacent 5′ residues as a template for telomeric repeat synthesis. Our findings reveal molecular requirements for template selection by telomerase and physically resolve templating from other RNA functions in catalysis.